Solution-enhanced dispersion by supercritical fluids: an ecofriendly nanonization approach for processing biomaterials and pharmaceutical compounds - Kankala RK (Dove Medical Press, 2018)
Ranjith Kumar Kankala,1–3,* Biao-Qi Chen,1,2,* Chen-Guang Liu,1,2 Han-Xiao Tang,1,2 Shi-Bin Wang,1–3 Ai-Zheng Chen1–3 1College of Chemical Engineering, Huaqiao University, Xiamen, People’s Republic of China; 2Institute of Biomaterials and Tissue Engineering, Huaqiao University, Xiamen, People’s Republic of China; 3Fujian Provincial Key Laboratory of Biochemical Technology (Huaqiao University), Xiamen, People’s Republic of China *These authors contributed equally to this work Abstract: In recent years, the supercritical fluid (SCF) technology has attracted enormous interest from researchers over the traditional pharmaceutical manufacturing strategies due to the environmentally benign nature and economically promising character of SCFs. Among all the SCF-assisted processes for particle formation, the solution-enhanced dispersion by supercritical fluids (SEDS) process is perhaps one of the most efficient methods to fabricate the biomaterials and pharmaceutical compounds at an arbitrary gauge, ranging from micro- to nanoscale. The resultant miniature-sized particles from the SEDS process offer enhanced features concerning their physical attributes such as bioavailability enhancement due to their high surface area. First, we provide a brief description of SCFs and their behavior as an anti-solvent in SCF-assisted processing. Then, we aim to give a brief overview of the SEDS process as well as its modified prototypes, highlighting the pros and cons of the particular modification. We then emphasize the effects of various processing constraints such as temperature, pressure, SCF as well as organic solvents (if used) and their flow rates, and the concentration of drug/polymer, among others, on particle formation with respect to the particle size distribution, precipitation yield, and morphologic attributes. Next, we aim to systematically discuss the application of the SEDS technique in producing therapeutic nano-sized formulations by operating the drugs alone or in combination with the biodegradable polymers for the application focusing oral, pulmonary, and transdermal as well as implantable delivery with a set of examples. We finally summarize with perspectives. Keywords: controlled release, anti-solvent, nanonization, drug delivery, polymeric carriers, parameters effect